‘Pop-up’ tourism or ‘invasion’? Airbnb in coastal Australia - Gurran, Nicole; Zhang, Yuting; Shrestha, Pranita (Annals of tourism research, 2020)
The global rise of peer to peer ‘home-sharing’ platforms such as Airbnb has accelerated negative forms of ‘touristification’ in major cities, often defying local regulation. But less is known about how such platforms affect regions beyond or peripheral to major population centres. This article addresses this question, examining 12 case-study communities in coastal Australia. Through in-depth interviews and focus groups with local stakeholders and planners, as well as analysis of Airbnb listings, tourism and housing data, we find that Airbnb style platforms intersect with, and impact, local governance, neighbourhoods and housing markets in different ways. We conceptualise these differences as a place-based taxonomy ranging from ‘pop-up’ to ‘invasive’ tourism, and highlight implications for research, policy and practice. •Examines impacts of Airbnb style rentals beyond Australia's major cities•Focuses on ‘touristification’ and gentrification impacts in 12 coastal cases•Finds that some communities benefit from ‘pop-up’ accommodation but others report tourism ‘invasion’•Impact patterns reflect local tourism practices and housing market pressures.